A Retrospective Analysis on the Urgent Need to Optimize Gestation Weight in Overweight/Obese Women to Lower Maternal-Fetal Morbidities: 59000 Singleton Term Pregnancies - Pierre-Yves Robillard; Gustaaf Dekker; Malik Boukerrou; Brahim Boumahni; Thomas C Hulsey; Marco Scioscia (Advancement and New Understanding in Medical Science Vol. 1, 2024)
Objective: This study primarily focuses on examining the criticalities of optimizing gestational weight for obese women to reduce fatal morbidities. We retrospectively did a simulation applying the optimal gestational weight gain (optGWG) equation (that we proposed in 2018) on our population, and observed if its effect on maternal/fetal morbidities in singleton term pregnancies (\(\)37 weeks). Design: This is a Retrospective observational study. Setting: The setting for this study was in a single large tertiary maternity unit in Reunion Island, Indian Ocean, overseas French department. Population or Sample: All consecutive singleton births delivered at the Centre Hospitalier Universitaire Hospitalier Sud Reunion’s maternity was the chosen population for this study. A standardized epidemiological perinatal database was used here. Methods: This study employed mathematical simulation on a 19-year historical cohort (2001-2019)’. Data was presented as numbers and proportions for categorical variables and as mean and Standard Deviation (SD) for continuous ones. Main Outcome Measures: Five Maternal/fetal morbidities were measured for this study. Results: Beginning with overweight women, and enlarging the effect with the rise of different obesities (class I to III) and considering maternal pre- pregnancy BMI (ppBMI), individualized counselling women on their GWG (optimal gestational weight gain, optGWG) lowers significantly maternal/ fetal morbidities: in a logistic regression model among overweight/obese women, with the outcome optGWG, several morbidities have a negative coefficient as independent factors: cesarean-section, birthweight \(\) 4000 g, term preeclampsia, lowering the effect of rising maternal ppBMI per increment of 5 kg/m² (coefficient -0.13), all p < 0.001. Dietary and lifestyle interventional studies have reduced GWG by 0.7kg or 3.7kg and had no effect on other pregnancy and birth outcomes including GDM, PE, PIH, LGA and macrosomic infants. We propose as a prediction to be verified in future prospective studies that a follow-up and counselling since the first prenatal visit should also lower gestational diabetes mellitus rates. Conclusion: We may have significant health (and cost) benefits by lowering c-section rates, term preeclampsia, macrosomic babies and LGA babies in overweight/obese women and low-birthweight babies in lean women. We may have much to win from reducing weight gain during pregnancy in overweight/obese women. It is urgent to verify and establish in all continents the specific linear curve of optGWG for each geographic/ethnic area.